PENGARUH KEPUTUSAN INVESTASI,KEPUTUSAN PENDANAAN, DAN TINGKAT SUKU BUNGA TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN TAHUN 2014-2017 - Vivi Noviyanti; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT            The purpose of this study was to find out how the Investment Decision, Financial Decision and Interest Rate has an effect on the Firm Value. The purpose of this study is to see (1)can find out how investment decision have an influence on the firm value, (2) can find out how financial decision have an influence on the firm value, (3) can find out how interest rate have an influence on the firm value.This research uses quantitative research. The population in this study is an Food and Beverages listed on the Indonesia Stock Exchange (IDX) period of 2014-2017. The sample in this study is 11 companies which uses purposive sampling technique. The method of research  is multiple linear regression analysis. The results of this study that Investment Decision, Financial Decision, and Interest Rate has an effect on Firm Value. Investment Decision has a significant and positive affect on Firm Value, Financial Decision has a significant and positive affect on Firm Value, and Interest Rate has a significant affect on Firm Value.